2012
DOI: 10.1128/jvi.05903-11
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Profiling and Analysis of Viral and Host Small RNAs during Human Cytomegalovirus Infection

Abstract: Human cytomegalovirus (HCMV) contributes its own set of microRNAs (miRNAs) during lytic infection of cells, likely finetuning conditions important for viral replication. To enhance our understanding of this component of the HCMV-host transcriptome, we have conducted deep-sequencing analysis of small RNAs (smRNA-seq) from infected human fibroblast cells. We found that HCMV-encoded miRNAs accumulate to ϳ20% of the total smRNA population at late stages of infection, and our analysis led to improvements in viral m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
137
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(148 citation statements)
references
References 42 publications
8
137
0
3
Order By: Relevance
“…It could very well be that the expression of this cluster is increased in some tumor cells but can be repressed by LMP-1. Interestingly, it was recently shown that another virus, human cytomegalovirus, could induce the expression of the miR-183-96-182 cluster, although in this case, it was a lytic infection (49) and the outcome of the infection was an arrest of the cell cycle, which would be the opposite of the outcome of EBV infection.…”
Section: Discussionmentioning
confidence: 94%
“…It could very well be that the expression of this cluster is increased in some tumor cells but can be repressed by LMP-1. Interestingly, it was recently shown that another virus, human cytomegalovirus, could induce the expression of the miR-183-96-182 cluster, although in this case, it was a lytic infection (49) and the outcome of the infection was an arrest of the cell cycle, which would be the opposite of the outcome of EBV infection.…”
Section: Discussionmentioning
confidence: 94%
“…However, deep sequencing of the small RNAs in infected cells readily identified viral miRNAs but detected only a limited number of other viral small RNAs. These small RNAs mapped to a restricted number of defined genomic loci, and whether they are bona fide Dicer products remains unclear (55). In plants (Arabidopsis), the pararetrovirus Cauliflower mosaic virus (CaMV) also produces long antisense transcripts (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian DNA viruses, including herpesviruses and polyomaviruses, produce viral miRNAs that are capable of modulating viral or host gene expression (64). Individual herpesviruses may encode multiple miRNAs; for example, human cytomegalovirus encodes 22 miRNAs in its 230-kb genome (55). In Drosophila, miRNA biogenesis involves the sequential processing of primary miRNA transcripts into pre-miRNAs by Drosha and its cofactor Pasha (together known as the Microprocessor complex) in the nucleus and the cleavage of pre-miRNA into mature miRNAs by cytoplasmic Dcr-1.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, herpesvirus miRNAs were found to regulate cellular genes involved in antigen processing and presentation. HCMV miRNA miR-US4-1 was reported to control MHC class I antigen presentation by targeting ERAP1 (30), but this finding is controversial (31). ERAP1 is an aminopeptidase that optimizes peptide-MHC class I binding, and its downregulation leads to a reduced killing of infected cells by virus-specific T cells (30).…”
Section: Viral Mirnas and Adaptive Immunitymentioning
confidence: 99%